WORD FORMATION PROCESSES OF JARGON FOUND IN PC WORLD MAGAZINE - KHAMILUDDIN, AJENG OKSA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study aims to find out the IT jargons, identify the word formation processes and the meaning of the jargons found in the headline’s article of PC World magazine issued in January 2013. The article is selected because it would be able to represent the jargons used in PC World magazine. This study was document analysis used qualitative approach with descriptive method. In this study, the writer found 48 (forty eight) IT jargons, and it showed that there are eight of fourteen word formation processes are used in forming the jargons; alphabetic abbreviation, compounding, coined word, multiple processes, acronym, derivation, blending, and generified word. The writer also found that co-text can be used to analyze the meaning. It can be concluded from the finding that jargon also exists in IT world in order to give a name of IT terms and word formation processes have an important roles in forming them.   Keywords: word formation processes, jargon, PC World Magazine.